Visible-light-promoted oxidative decarboxylation of arylacetic acids in air: Metal-free synthesis of aldehydes and ketones at room temperature - He, Shuaiqi; Chen, Xiaolan; Zeng, Fanlin; Lu, Peipei; Peng, Yuyu; Qu, Lingbo; Yu, Bing (Chinese chemical letters, 2020)
A metal-free 4CzIPN-catalyzed oxidative decarboxylation reaction of arylacetic acids to aromatic aldehydes and ketones was developed at room temperature with air as oxidant under blue-light irradiation. [Display omitted] A metal-free photocatalytic oxidative decarboxylation reaction at room temperature was developed for the synthesis of aromatic aldehydes and ketones from the corresponding arylacetic acids. The reaction was realized under blue-light irradiation by adding 1 mol% of 4CzIPN as photocatalyst and air as oxidant. This reaction represents a novel decarboxylation of a sp3-hybridized carboxylic acids without traditional heating, additional oxidants, and metal reagents under mild conditions.